Biodegradability of some antibiotics, elimination of the genotoxicity and affection of wastewater bacteria in a simple test - Kümmerer, Klaus; Al-Ahmad, Ali; Mersch-Sundermann, Volker (Chemosphere, 2000)
Most antibiotics and their metabolites are excreted by humans after administration and therefore reach the municipal sewage with the excretions. Only little is known about their biodegradability in aquatic environments. It was recognised that genotoxic substances may represent a health hazard to humans but also may affect organisms in the environment. Therefore, the biodegradability of some clinically important antibiotic drugs (ciprofloxacin, ofloxacin, metronidazole) and hereby the elimination of their genotoxicity was investigated as the first step of an environmental risk assessment using the Closed Bottle test (CBT) (OECD 301 D) and the SOS chromotest. Additionally, to assess toxicity of the antibiotics tested against aquatic bacteria (i) a growth inhibition test (GIT) with Pseudomonas putida was conducted, (ii) a toxicity control was used in the CBT and (iii) the colony forming units (CFUs) were monitored in the test vessels. Worst case concentrations of the antibiotics in hospital effluents were estimated and compared with minimum inhibitory concentrations for susceptible pathogenic bacteria and with the genotoxic potency in the SOS chromotest. Both the concentrations calculated for hospital effluents and the adverse effects in bacteria were in the same order of magnitude. None of the test compounds were biodegraded. The genotoxicity was not eliminated